Effect of dexamethasone on cardiovascular response induced by norepinephrine in nucleus tractus solitarii - Ou-yang Ming; Ge Guang-hui; Wang Shao (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of dexamethasone on cardiovascular response induced by norepinephrine (NE) in nucleus tractus solitarii (NTS). METHODS: The variations of cardiovascular action caused by these drugs were observed after injection of mifepristone (Mif), dexamethasone (Dex), bicuculline (Bic), and NE into the medial and intermediate NTS. RESULTS: Microinjection of Dex (0.39 mmol.L-1, 0.1 microL) into the medial and intermediate NTS abolished the vasodepressed response to NE (8 mmol.L-1, 0.1 microL) microinjected into the same area 10 min later, and the inhibition did not disappear until 4 h. The rapid inhibitory effects of Dex on NE vasodepression was not antagonized by Mif (4.66 mumol.L-1, 0.1 microL), but it was blocked by Bic (3.24 mumol.L-1, 0.1 microL). CONCLUSION: Dex abolished cardiovascular response to NE microinjected into NTS which may be mediated by GABAA receptor.